Factor Structure and Basic Psychometric Properties of the Transition Assessment and Goal Generator. (May 2018) - Hennessey, Maeghan N.; Terry, Robert; Martin, James E.; McConnell, Amber E.; Willis, Donna M.
We examined the theoretical factor structure fit and psychometric properties of the Transition Assessment and Goal Generator (TAGG). In the first study, 349 transition-aged students with disabilities, their special educators, and family members completed TAGG assessments, and using exploratory factor analysis (EFA)/confirmatory factor analysis (CFA), a simple eight-factor structure emerged. In 2 subsequent years, independent samples of students with disabilities (Study II, N = 257; Study III, N = 846), their special educators, and family members completed the TAGG, and the TAGG structure replicated in both years across all versions using CFAs. The results provide evidence of construct validity and reliability. We discuss implications of the results and identify future research needs.